Pengaruh Capital Adequacy Ratio, Biaya Operasional Pendapatan Operasional dan Non Performing Loan Terhadap Profitabilitas Pada Sektor Perbankan yang Terdaftar di Bei Tahun 2017-2022 - Marbun, Patar; K, Khairunnisa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the effect of the Capital Adequacy Ratio, Operating Costs, Operating Income and Non-Performing Loans on the Profitability of the Banking Sector Listed on the IDX in 2017-2022. The research sample in this number is 15 companies with a research period of 5 years. The method used in selecting the sample in this study is purposive sampling method. The data used is secondary data, by collecting company financial reports starting from 2017-2022 obtained through the official website of the Indonesia Stock Exchange. The data analysis method used in this study is the classical assumption test, multiple linear regression analysis and hypothesis testing where the data is processed using SPSS. The results of this study indicate that the Capital Adequacy Ratio has no positive and insignificant effect on return on assets. Meanwhile Operating Costs Operating Income has a negative and significant effect on return on assets. Meanwhile, non-performing loans have a negative and significant effect on return on assets. The results of the F test show that the Capital Adequacy Ratio, Operating Expenses, Operating Income and Non-Performing Loans have a positive and significant influence on return on assets in the banking sector listed on the IDX in 2017-2022.